EVALUASI VALIDITAS ISI DAN KONSTRUK SERTA PRATIKALITAS LKPD KESETIMBANGAN KIMIA BERBASIS INKURI TERBIMBING UNTUK MELATIH KETERAMPILAN BERPIKIR KRITIS SISWA - Ummarah, K (Journal of Technique Research (JTR), 2019)
This study aims to determine the level of content validity and construct validity of guided inquiry-based worksheet (LKPD) based on chemical equilibrium material to train students' critical thinking skills. This research is Research and Development (R & D) research. The study was conducted at SMAN 1 PADANG. The data taken is the data from the test results of content validity and construct validity by the validator. The instruments used are questionnaires filled by lecturers and teachers. The data of this study will be analyzed using kappa moments. The results of the analysis show that it is judged by the content quality, presentation, language, and graphics, respectively 0.834, 0.853, 0.885, 0.895. In accordance with the results of the validity analysis, the LKPD is categorized as very valid. The guided inquiry LKPD on chemical equilibrium material to train students' critical thinking skills is deemed feasible based on their validity. The result of the practicality is 0,85 , indicating that the LKPD is vey pratical.